Perspectives About Health Care Provision in Dementia Care in Spain: A Qualitative Study Using Focus-Group Methodology. (May 2016) - Risco, Ester; Cabrera, Esther; Farré, Marta; Alvira, Carme; Miguel, Susana; Zabalegui, Adelaida
Background: The aim of this study is to identify the barriers and facilitators in dementia care with respect to information provision, communication, and collaboration from the perspectives of the person with dementia, family caregivers, and health care professionals over the course of the illness. Methods: A qualitative study using Focus-Group methodology was carried out in people with dementia, family caregivers, and health care providers. Results: The categories that emerged from the analysis were insufficient information provided, specific dementia care needs, and acceptance of long-term care institutionalization from the people with dementia and caregivers' groups and insufficient communication between health care providers, differential information according to disease stage, and home care coordination from the health care providers' groups. Conclusion: The family is a key element in successful care coordination during dementia care provision. New effective strategies including self-management and emergent roles, such as case managers, could bring great benefits to people with dementia, caregivers, and health care providers.